Mask of treachery - "Costello, John" (New York, 1988)
Newly discovered British and American reports, scores of interviews, and expert analysis substantiate an account of the espionage network created by Anthony Blunt and of that network's infiltration of British and American institutions.
Keywords: "Spies Great Britain, France, German, Canada, USA, USSR b"